Defining a holoprosencephaly locus on human chromosome 14q13 and characterization of potential candidate genes - Kamnasaran, Deepak; Chen, Chih-Ping; Devriendt, Koenraad; Mehta, Lakshmi; Cox, Diane W. (Genomics (San Diego, Calif.), 2005)
Holoprosencephaly (HPE) is the most common developmental field defect in patterning of the human prosencephalon and associated craniofacial structures. The genetics is complex, with 12 loci defined on 11 chromosomes. We defined a locus for HPE (HPE8) on human chromosome 14q13 between markers D14S49 and AFM205XG5, by mapping deletion intervals of affected subjects with proximal chromosome 14q interstitial cytogenetic deletions. A 35-BAC contig was built by chromosome walking. By annotation of the 2.82-Mb minimal critical region, we identified 28 possible genes. Seven genes were expressed in human fetal brain: NPAS3, SNX6, C14ORF11, C14ORF10, PAX9, NKX2.1, and C14ORF19, the last an apparent gene fragment. Molecular embryology, animal modeling, and human mutation studies were reported elsewhere for PAX9 and NKX2.1. We focused on three genes, SNX6, NPAS3, and C14ORF11, as potential candidates for HPE. Genomic structure, human expression patterns, protein cellular localization, and embryonic expression patterns of orthologous murine genes were determined, showing that the three genes have properties similar to those of known HPE genes.